La tutela della vittima nell’ordinamento europeo: quale impatto della direttiva 2012/29/UE? - Paoletti, Silvia (Cultura giuridica e diritto vivente, 2016)
[The protection of the victim in European Law: what will be the impact of Directive 2012/29 / EU?] Adopted by the European Parliament and the Council of Europe a decade after the 2001/220 / JHA Framework Decision, Directive 2012/29 / EU complements the European Statute as regards the victims of crime. The latters are granted a number of prerogatives intended to ensure that they take part in the legal proceedings in a conscious and mindful way and to avoid the risk of so-called secondary victimization. Italy has just adopted measures to implement the Directive, because the increased protection for crime victims concerns a constitutionally guaranteed principle.